GENETIC FACTORS OF HEMOSTASIS DISORDERS IN WOMEN OF REPRODUCTIVE AGE - Akhmadzhonova, G.M.; Uljabaev, J.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. According to studies, mutations in the genes of the hemostasis system are associated with an increased risk of venous thromboembolism and infertility. However, the diagnosis of thrombophilia is often erroneously established due to overdiagnosis, which can lead to unjustified and potentially harmful prescription of drugs. The aim of the work is to study the hemostasis system in pregnant women with complicated hemostatic history. Materials and methods. Data from 59 pregnant and postpartum women who were in Maternity Hospital No. 2 in Andijan were analyzed. Anamnesis, anthropometric parameters, results of genetic testing for polymorphisms of the genes of the hemostasis system and risk factors for coagulopathic disorders were assessed. Results and discussion. When assessing the body mass index (BMI), it was normal in 49.4% of the postpartum women, and exceeded the norm in 50.6%. Polymorphism G-455A of the FGB gene was almost not detected. Mutation of the ITGA2 gene was detected in 48.1% of cases. Polymorphism of the PAI-1 gene was recorded in 84.8% of cases. Conclusion. Hereditary disorders of the hemostasis system are a key risk factor for thromboembolic complications. Antithrombotic therapy started before pregnancy reduces the likelihood of obstetric complications and contributes to a favorable pregnancy outcome.